2019
DOI: 10.1002/jcp.29393
|View full text |Cite
|
Sign up to set email alerts
|

Signatures of altered DNA methylation gene expression after central and peripheral nerve injury

Abstract: Nerve damage can lead to movement and sensory dysfunction, with high morbidity and disability rates causing severe burdens on patients, families, and society. DNA methylation is a kind of epigenetics, and a great number of previous studies have demonstrated that DNA methylation plays an important role in the process of nerve regeneration and remodeling. However, compared with the central nervous system, the peripheral nervous system shows stronger recovery after injury, which is related to the complex microenv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…DNA methylation, histone modification and non-coding RNA regulation have been studied in previous epigenetic research (31,(52)(53)(54). In our previous studies, genome-wide methylation analyses and iTRAQ-based proteomics profiling of Schwann cells after PNI were performed (23,35).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA methylation, histone modification and non-coding RNA regulation have been studied in previous epigenetic research (31,(52)(53)(54). In our previous studies, genome-wide methylation analyses and iTRAQ-based proteomics profiling of Schwann cells after PNI were performed (23,35).…”
Section: Discussionmentioning
confidence: 99%
“…DNA methylation, which directs transcriptional silencing via heterochromatin formation, is a genetic marker for the growth and development of a number of eukaryotes (27)(28)(29). As one of the earliest epigenetic modifications to be recognized, DNA methylation has been observed in numerous organisms (30,31). Methylation of eukaryotic DNA typically occurs at position 5 of cytosine to produce 5-methylcytosine (32).…”
Section: Identification Of Adhesion-associated Dna Methylation Pattermentioning
confidence: 99%
“…Whether neurons and axons can regenerate after SCI depend not only on their original growth ability, but also on the neurovascular microenvironment and epigenetic changes, which is mainly embodied in DNA methylation and histone acetylation ( 27 ). Among these, DNA methylation affects many aspects of neural stem cell maintenance and proliferation, neuronal differentiation and maturation, and synaptogenesis ( 28 ). Decitabine is a demethylating drug that can inhibit DNA methyltransferase, reduce DNA methylation, and inhibit tumor cell proliferation, and it has been the primary drug for elderly AML patients ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…( 8 ). Some studies have indicated the importance of investigating the effect of pathways of interest on the occurrence and development of MMD ( 14 16 ). However, information regarding the significantly different methylation sites in adult ischemic MMD remains scarce.…”
Section: Discussionmentioning
confidence: 99%